A comprehensive review of treatment options for recalcitrant nongenital cutaneous warts - Kanchana Leerunyakul (2020)
© 2020, © 2020 Taylor & Francis Group, LLC. Introduction: The treatment of recalcitrant nongenital cutaneous warts has always been challenging for dermatologists as they often recur and relapse. Multiple treatment options have been investigated to improve the outcome. This review provides an overview of the current treatment modalities and summarizes the efficacy and side effects of each treatment option for recalcitrant nongenital cutaneous warts. Methods: A PubMed search was performed through July 2019 to include all English language reports investigating the treatment for recalcitrant nongenital cutaneous warts, regardless of design. Results: A total of 144 studies were included in this review. The treatment options for recalcitrant nongenital cutaneous warts can be divided into three groups: destructive treatment, immunotherapy, and cytotoxic agents. Although both destructive therapies and cytotoxic agents demonstrated high complete response rates, immunotherapy, which is a minimally invasive method, was superior in terms of the clearance of distant warts. Intralesional mumps–measles–rubella injections and purified protein derivatives currently demonstrate high efficacy with well-established clinical evidence. Conclusions: Many upcoming treatment modalities, especially immunotherapy, are promising. However, more comparative studies are required to verify the efficacy and safety profile.